The Effect of Law Number 7 of 2021 on Harmonization of Tax Regulations on Fiscal Justice in Indonesia - Judijanto, Loso; Muhtadi, Muhamad Ammar (Westscience Press, 2024)
Law No. 7 of 2021 on Harmonisation of Tax Regulations is a landmark reform in Indonesia aimed at enhancing tax compliance, promoting fiscal justice, and aligning the country’s tax framework with international standards. This study provides a jurisdictional analysis of the law, examining its key provisions, impact on tax compliance, revenue collection, and socio-economic implications. The results show that the law has significantly broadened the tax base, improved tax transparency, and introduced progressive measures to promote equity, including a carbon tax and revised income tax brackets. However, challenges remain in ensuring that the benefits are distributed equitably across all income groups and sectors. The study concludes that while Law No. 7 of 2021 represents a significant step toward achieving fiscal justice, further refinement and support for smaller enterprises are required to fully realize its potential.